2016
DOI: 10.1681/asn.2016010082
|View full text |Cite
|
Sign up to set email alerts
|

Acute Adaption to Oral or Intravenous Phosphate Requires Parathyroid Hormone

Abstract: Phosphate (Pi) homeostasis is regulated by renal, intestinal, and endocrine mechanisms through which Pi intake stimulates parathyroid hormone (PTH) and fibroblast growth factor-23 secretion, increasing phosphaturia. Mechanisms underlying the early adaptive phase and the role of the intestine, however, remain ill defined. We investigated mineral, endocrine, and renal responses during the first 4 hours after intravenous and intragastric Pi loading in rats. Intravenous Pi loading (0.5 mmol) caused a transient ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 49 publications
6
85
1
Order By: Relevance
“…A recent study by Thomas and colleagues demonstrated that the acute phosphaturic response is dependent on PTH‐mediated downregulation of renal phosphate transporters . Our data indicate that the PTH response is dependent on the resting level of circulating PTH.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…A recent study by Thomas and colleagues demonstrated that the acute phosphaturic response is dependent on PTH‐mediated downregulation of renal phosphate transporters . Our data indicate that the PTH response is dependent on the resting level of circulating PTH.…”
Section: Discussionsupporting
confidence: 58%
“…A recent study by Thomas and colleagues demonstrated that the acute phosphaturic response is dependent on PTHmediated downregulation of renal phosphate transporters. (6) Our data indicate that the PTH response is dependent on the resting level of circulating PTH. Specifically, it is the relative change after an oral phosphate load, rather than the absolute magnitude of the PTH change, that is positively correlated with the excretion of the circulating phosphate.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Our findings show that although the kidney responds to changes in intestinal phosphate load, the response appears to occur only following exposure to very high levels of ingested phosphate. Interestingly, a recent study by (Thomas et al 2016a) has shown that the phosphaturia caused by intravenous infusion of phosphate is associated with elevated plasma phosphate and PTH concentrations, but that while intragastric administration of the same phosphate load increases urinary phosphate excretion to the same extent as when given intravenously, it is related to elevated plasma PTH and not plasma phosphate concentrations, highlighting the key role for PTH in the phosphaturic response. In keeping with this suggestion is the finding that in humans, phosphaturia caused by an acute intestinal phosphate load is also associated with changes in plasma phosphate and PTH concentrations (Nishida et al 2006;Bevilacqua et al 2010;Scanni et al 2014).…”
Section: G J Lee and Othersmentioning
confidence: 99%